Pengaruh Fasilitas Konser Internasional Terhadap Kepuasan Wisatawan Indonesia Di Singapura - Niken; Jasmine Nashwa Mutiara Seno; Safira Nurhaliza; Chikita Alamanda Arafa; Dina Hariani (Institut Citra Internasional, 2025)
This study examines the influence of international concert facilities on Indonesian tourists' satisfaction attending concerts in Singapore, amid rising concert tourism influenced by facility quality (cleanliness, infrastructure, comfort, environment). The objective is to measure facilities' contribution to overall satisfaction. Employing a quantitative approach with purposive sampling (100 Indonesian respondents), Likert-scale questionnaire data were analyzed via validity, reliability, normality tests, simple linear regression, t-test, and coefficient of determination. Results reveal a positive-significant effect (sig=0.000; t=20.384; R²=0.809), with 80.9% of satisfaction variance explained by facilities. Conclusion: Optimal facility management enhances visitor experience, bolstering concert tourism and Singapore's competitiveness.